Pelatihan Pembuatan Media Alat Peraga Edukatif (APE) Untuk Anak Usia Dini Bagi Kepala Sekolah Dan Guru Taman Kanak-Kanak Berbasis Kewirausahaan di Kecamatan V Koto Kampung Dalam Kabupaten Padang Pariaman - Nenny Mahyuddin; Rani Sofya Sofya (Jurnal Ecogen, 2019)
Media is an important thing in supporting learning. Media is an intermediary/introduction of learning messages to children so that there is a common perception given by the teacher and received by the child. Provision of media facilities requires the ability of creative teachers to create learning medium so that the material is distributed or delivered to children. Consider in designing the media not only in terms of children's interests but also the compatibility between the media and the material that will be conveyed so that it can be delivered fundamentally accepted by the child. In fact there are still many teachers who do not yet have the ability of creativity in designing educational learning media in learning in kindergarten. Most teachers only use mediocre and monotonous media so that children are not motivated in learning. This greatly affects the success of children's learning. The teacher's ability to design instructional media greatly influences the outcome of learning. Therefore we need special training for teachers to develop and hone the ability of teacher creativity to design educational learning media that are able to support learning in early childhood. The training is carried out in the form of educational learning media design activities that begin from giving examples of educational media, the teacher tries to design media for all themes, determines the message and information to be conveyed, selects tools and materials from various sources that will be used until the teacher makes the media and how to use the media. The training will hone and invite the teacher to think creatively in creating an educational learning media in children's learning Keyword: educative viewer media, entrepreneur